Money, power and conflict among married couples in urban Sarawak - Wee, Ling Min (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study investigates the relationship between money, power and equality in marriage by interviewing 40 married working couples in urban Sarawak. The aim is to examine if women’s access to economic resources through participation in the labour force has resulted in more equitable distribution of marital power in their marriage. The study focuses on three aspects of the marital relationship: control and organisation of money; household decision making and personal spending. The findings suggest that: firstly, much of marital power is hidden or invisible and that conflicts are seldom reported. In fact, a lack of conflict might be an indication of the existence of power and an unequal relationship. As such, to better understand the nature of marital power, it is important to study both observable power outcomes such as control over decision making and the underlying power mechanisms that lead to these outcomes. Secondly, the balance of marital power is more closely related to gender ideologies and religious teaching than economic factors. This suggests that women’s access to economic resources through paid work need not necessarily result in greater bargaining power in their marriage.